Globin Digest Improves Visceral Adiposity Through UCP1 Upregulation in Diet-Induced Obese Zebrafish and Mice - Zang, Liqing; Shimada, Yasuhito; Nakayama, Hiroko; Matsuoka, Izumi; Kim, Youngil; Chu, Djong-Chi; Juneja, Lekh Raj; Tsuruta, Rika; Sasakawa, Yuka; Kuroyanagi, Junya; Nishimura, Norihiro (Frontiers in Nutrition, 2021)
Globin digest (GD), a bioactive oligopeptide derived from porcine hemoglobin proteins, has been demonstrated to have beneficial effects on improving postprandial hyperlipidemia, hyperglycemia, and liver injury. We previously reported the lipid-lowering effects of GD using a zebrafish obesogenic test. Here, we sought to evaluate the effect of GD on visceral adiposity and the underlying molecular mechanisms using zebrafish and mouse obesity models. GD ameliorated dyslipidemia and suppressed the accumulation of visceral adipose tissue (VAT) in adult obese zebrafish. Transcriptomic analysis by RNA sequencing of GD-treated adult zebrafish revealed that GD upregulated UCP1-related pathways. Further, we performed mouse experiments and found that GD intake (2 mg/g body weight/day) was associated with lowered plasma triglyceride and total cholesterol levels, decreased VAT accumulation, and improved adipocyte hypertrophy with the upregulation of Ucp1 expression in white adipose tissue at both the mRNA and protein levels. Taken together, these results indicate that GD improves visceral adiposity by upregulating UCP1 expression, providing a novel perspective on combating obesity.